Heme oxygenase induction attenuates TNF-α-induced hypertension in pregnant rodents - George, Eric M.; Stout, Jacob M.; Stec, David E.; Granger, Joey P. (Frontiers in Pharmacology, 2015)
Pre-eclampsia is a hypertensive disorder of pregnancy initiated by placental insufficiency and chronic ischemia. In response, several pathways activated in the placenta are responsible for the maternal syndrome, including increased production of the anti-angiogenic protein, sFlt-1, and inflammatory cytokines, especially tumor necrosis factor-alpha (TNF-α). Previous studies have demonstrated that heme oxygenase (HO) induction can block TNF-α pathways in vitro and attenuate placental ischemia-induced sFlt-1 in vivo. Here, we investigated whether HO-1 induction could attenuate TNF-α-induced hypertension in pregnant rats. In response to TNF-α infusion (100 ng/day i.p.), maternal mean arterial pressure (MAP) increased vs control animals (104±3 vs. 119±3 mmHg). HO-1 induction had no effect in control animals, but significantly decreased MAP in TNF-α-infused animals (104±3 mmHg). Placental vascular endothelial growth factor (VEGF) was decreased in response to TNF-α infusion (92±4 vs. 76±2 pg/mg). Placental sFlt-1 was increased by TNF-α infusion (758±45 vs. 936±46 pg/mg, p<0.05), which was significantly reduced by HO-1 induction (779±98 pg/mg). In contrast, HO-1 induction had no significant effect on placental VEGF in TNF-α-infused animals. Taken together, these data suggest that one of the key mechanisms by which HO exerts cytoprotective actions in the placenta during inflammation due to chronic ischemia is through suppression of sFlt-1. Further work elucidating the bioactive metabolites of HO-1 in innate inflammatory responses to placental ischemia is warranted.